Preparation method of pore size-adjusted and metal-loaded graphite felt flow battery electrode

By pretreating and separating pores, loaded neodymium oxide and oxygen-deficient CoMnOx, and electrodeposition bismuth, the problem of insufficient conductivity and stability of the flow battery electrode is solved, and efficient electrochemical performance and long-life electrode materials are achieved.

CN120319827BActive Publication Date: 2025-08-26HANGZHOU BOILER GRP CO LTD

Patent Information

Application Number
CN202510795486.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-16
Publication Date
2025-08-26
Estimated Expiration
2045-06-16

AI Technical Summary

Technical Problem

The conductivity and stability of existing flow battery electrodes are insufficient, which affects their performance and efficiency, especially in redox reactions.

Method used

Through the steps of pretreatment and separation of pores, loaded neodymium oxide, loaded oxygen defect CoMnOx, and electrodeposition of bismuth, graphite felt electrodes with various pore sizes are formed to enhance the conductivity and stability of the electrodes.

Benefits of technology

The electrochemical performance and energy efficiency of the flow battery electrode have been significantly improved, the energy efficiency has been increased to more than 85%, and the number of stable cycles has been increased to more than 1,440 times.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120319827B_ABST
    Figure CN120319827B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a pore-adjustable and metal-loaded graphite felt flow battery electrode, comprising the following steps: (1) pretreatment and pore separation: mixing graphite felt with an alkaline solution, magnetically stirring, heating, cooling to room temperature, and re-treating to obtain a pore-separated material; (2) loading neodymium oxide: immersing the pore-separated material in a solution containing a neodymium salt and a polyamino acid, heating, cleaning, and drying to obtain a neodymium oxide-modified electrode material; (3) loading oxygen-deficient CoMnOx: applying a mixed slurry containing manganese and cobalt to an electrode sheet, heating, cleaning, and drying to obtain an oxygen-deficient CoMnOx-loaded electrode; and (4) electrodepositing the oxygen-deficient CoMnOx-loaded electrode to obtain a novel graphite felt electrode with bismuth deposition. The electrode product obtained by the method of the present invention has an energy efficiency of more than 85%, and the number of stable cycles at which the energy efficiency is maintained can exceed 1440 times.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a liquid flow battery energy storage technology, and in particular to a method for preparing a pore-adjustable and metal-loaded graphite felt liquid flow battery electrode. Background Art

[0002] The emerging liquid flow battery is an important technology for improving the storage and conversion capabilities of clean energy. The properties of the electrode material, a core component, have a significant impact on the operational activity, stability, and efficiency of the flow battery. Carbon electrodes are a common type of flow battery electrode. To achieve optimal performance, they require modification and treatment, such as physical and chemical treatment, metal doping, the introduction of porous materials, and the introduction of functional groups to increase the electrode surface area, reduce impedance, and reduce polarization. In recent years, the introduction of certain metals, such as group IIIB neodymium, has been shown to enhance the catalytic performance of the electrode by participating in redox reactions. However, as an oxygen binder, the conductivity and stability of neodymium-modified electrodes remain insufficient. Further treatment, namely loading composite metal oxides with oxygen vacancies to improve their conductivity, and further enhancing the conductivity and electrode stability through electrodeposition of metals, is an effective approach that can simultaneously address the problems of insufficient stability and low performance of existing flow battery electrodes. However, no relevant literature has yet addressed this treatment method. Summary of the Invention

[0003] In order to overcome the problems in the prior art, the present application provides a method for preparing a pore size-adjusted and metal-loaded graphite felt flow battery electrode.

[0004] In order to achieve the above object, the present invention provides a method for preparing a pore size-adjusted and metal-loaded graphite felt flow battery electrode, which comprises the following steps:

[0005] Step (1), pretreatment and pore separation: mixing the graphite felt with alkali solution, magnetically stirring and then heating, cooling to room temperature and then mixing with alkali solution again, magnetically stirring and heating again to obtain a pore separation material;

[0006] Step (2), loading neodymium oxide: dissolving neodymium salt and polyamino acid in an alcohol solution, adding ammonia water dropwise and immersing the porous material therein, heating, washing and drying to obtain a neodymium oxide-modified electrode material;

[0007] Step (3), loading oxygen-deficient CoMnOx: applying a mixed slurry containing manganese and cobalt on an electrode sheet, heating, washing, and drying to obtain an oxygen-deficient CoMnOx loaded electrode;

[0008] Step (4), bismuth deposition: 1-butyl-3-methylimidazole chloride and bismuth oxide are dissolved in alkaline solution to form a three-electrode system electrolyte, the electrode loaded with oxygen defect CoMnOx is electroplated, and the bismuth-deposited graphite felt electrode is obtained by washing and drying.

[0009] Preferably, in step (1), the alkali solution includes sodium hydroxide, and the sodium hydroxide treatment is performed by first mixing 1 g of graphite felt with 100-200 mL of 0.5-1 mol / L sodium hydroxide solution and treating under magnetic stirring for 30-40 min; the second treatment method is the same, except that the concentration of the sodium hydroxide solution is adjusted to 1-2 mol / L.

[0010] Preferably, in step (1), the heating is performed for the first time at 760-780°C in a nitrogen atmosphere for 2-3 h, with the heating rate controlled at 2-3°C / min, and the second time at the same temperature with the heating rate controlled at 3-5°C / min.

[0011] Preferably, in step (2), the neodymium salt includes one or more of neodymium nitrate and neodymium chloride, the alcohol solution includes one or more of ethanol and isopropanol, and the heating is performed in a nitrogen atmosphere at 480-520°C for 2-3 h, with the heating rate controlled at 3-5°C / min.

[0012] Preferably, in step (2), the mass loading per unit area of ​​neodymium oxide is 0.17-0.19 mg / cm 2 .

[0013] Preferably, in step (3), the mixed slurry containing manganese and cobalt is obtained by adding potassium permanganate, manganese sulfate, cobalt sulfate and sodium citrate to water and ethanol, and performing a hydrothermal reaction in an oven at 150-160° C. for 8-10 h.

[0014] Preferably, the coating mass loading per unit area of ​​the mixed slurry is 0.38-0.42 mg / cm 2 The heating is performed at 390-430° C. for 2.5-3 h at a heating rate of 2-3° C. / min.

[0015] Preferably, in step (4), the three-electrode system electrolyte is an aqueous solution of sodium carbonate, potassium hydroxide, 1-butyl-3-methylimidazole chloride, bismuth oxide and ethanolamine, with a pH of 13.6-14.

[0016] Preferably, in step (4), the electrodeposition is carried out at 2 to 3 A / dm 2 The pulse current density was repeated for several cycles, and the temperature was kept at 40-50°C to control the electrodeposition amount of bismuth to 0.26-0.30 mg / cm 2 .

[0017] Preferably, in step (1), ethanol and deionized water are used for cleaning, and dilute hydrochloric acid and deionized water are used for impurity removal. After treatment, two different ranges of pores are formed. Pores with a pore size > 1 μm can serve as channels for the electrolyte of the flow battery, and pores with a pore size of 5-10 nm provide a large number of active sites for redox reactions.

[0018] Preferably, in step (2), the electrode is immersed in a mixture of 2.75-2.85 g of anhydrous neodymium nitrate, 1.26-1.34 g of anhydrous neodymium chloride and 0.28-0.36 g of polyamino acid dissolved in 50 mL of ethanol and isopropanol (the volume ratio of the two is 1-1.5:1), and then 4.5-5.5 mL of ammonia water is dripped into it in a closed environment.

[0019] Preferably, in step (3), the mixed slurry is prepared by adding 1.25-1.35 g of potassium permanganate, 0.66-0.70 g of manganese sulfate monohydrate, 0.57-0.61 g of cobalt sulfate hexahydrate, and 0.36-0.42 g of sodium citrate to 35-45 mL of deionized water and 5-15 mL of anhydrous ethanol. Preferably, the mixed solution is added to a hydrothermal reactor, sealed, and kept warm in an oven at 150-160°C for 8-10 h.

[0020] Preferably, in step (4), the mixed solution is prepared by adding 30-40 mL of 0.25-0.3 mol / L sodium carbonate, 30-40 mL of 0.28-0.32 mol / L potassium hydroxide, 0.23-0.29 g of 1-butyl-3-methylimidazole chloride, 1.8-2.2 g of bismuth oxide, and 3-5 mL of ethanolamine to a container and adjusting the volume to 1 L. The pH value is adjusted to 13.6-14 using 3 mol / L potassium hydroxide solution.

[0021] Preferably, in step (4), the electrodeposition mixture is used as the electrolyte of the three-electrode system and the electrode obtained in step (3) is placed in the electrolytic cell three-electrode system perpendicular to the flow direction of the electrolyte, and a pulse power supply of 2-3 A / dm is used. 2 The pulse current density was cycled for several times and kept at 40-50℃, and the electrodeposition amount of bismuth was controlled at 0.26-0.30 mg / cm 2 The energy efficiency of the electrode was ultimately increased to 85.3-86.6%, and the number of stable cycles increased significantly to more than 1,440 times.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] After two treatments of sodium hydroxide and high temperature, a large number of small pores of two different sizes are formed. Pores with a pore size >1 μm can serve as channels for the electrolyte of the flow battery, while pores with a pore size of 5-100 nm provide a large number of active sites for redox reactions. The electrolyte channels expand the active area of ​​the electrochemical reaction and improve the utilization rate of the electrolyte; the small pores provide sites for subsequent further electrode treatment, which enhances the kinetics of the redox reaction; the specific surface area after treatment increases by 180% compared with the original specific surface area, reaching 75.6 m 2 / g.

[0024] Loading neodymium oxide on the high-surface-area electrodes mentioned above can enhance electrochemical performance. Neodymium oxide forms Lewis acids with acid ions and reacts with diffused redox couples, adjusting the reaction potential. Neodymium, as an oxygen binder, can enhance charge-discharge performance and energy efficiency by participating in catalytic reactions. By loading cobalt manganese oxide with oxygen defects to enhance the bonding between neodymium and the electrode, conductivity and stability are improved, and the number of stable cycles maintaining energy efficiency within 95% of the first cycle has increased by 780 compared to the original electrode.

[0025] The electrodeposition of bismuth can further improve the conductivity and stability of the above-mentioned electrodes. The advantages of bismuth such as low toxicity, low cost, high conductivity and high acid resistance enable it to significantly improve the electrochemical performance and stability of the above-mentioned electrodes. The electrodeposited bismuth-based material has good catalytic performance for the redox reaction of the electrode pair and provides a larger active area. The coupling with the above-mentioned cobalt-manganese metal enhances the catalytic activity, reduces the reaction overpotential, and inhibits the hydrogen evolution reaction in the electrochemical process. The energy efficiency of the final electrode product is increased to more than 85%, and the number of stable cycles that maintain the energy efficiency within 95% of the first cycle is further increased to more than 1440 times. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The scanning electron microscope microscopic images of the present invention are shown in Figure 1. (a) shows the electrode structure obtained in Example 1. A microscopic needle-like structure of 0.5 to 4 μm can be seen, and there are a large number of pores on the surface. The specific surface area test shows that the electrode specific surface area is about 75.6 m 2 / g; (b) is the electrode structure obtained in comparative example 1. Similar microscopic needle-like structures can be seen covering the electrode surface. The number of pores is lower than that in (a). The electrode specific surface area is about 52.6 m 2 / g.

[0027] Figure 2 The peak current curves of the current-voltage curves of Example 1, Comparative Example 1 and Comparative Example 4 at different scan rates. 2+ / VO2 + and V 3+ / V 2+The peak potential of the electrode pair is the lowest, while that of comparative example 4 is the highest, indicating that example 1 has the best electrochemical performance.

[0028] Figure 3 The present invention is at a current density of 100 mA / cm 2 According to the energy efficiency change curve after multiple cycles, Example 1 can maintain the energy efficiency within 95% of the first cycle for 1505 stable cycles, which is much higher than the 772 times of Comparative Example 4.

[0029] Figure 4 The technical roadmap for preparing the electrode of the present invention. DETAILED DESCRIPTION

[0030] To better illustrate the purpose, technical solutions and advantages of the present invention, the present application will be further described below in conjunction with specific embodiments. Those skilled in the art should understand that the embodiments are only intended to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0031] In the present invention, the charge and discharge performance, energy efficiency and stability are obtained by connecting a liquid flow battery system and reading relevant data on an electrochemical workstation. The conductivity is obtained by using a probe method to test the conductivity, and the specific surface area is obtained using a specific surface area and pore tester BET.

[0032] The present invention provides a novel graphite felt flow battery electrode with pore size adjustment and metal loading, comprising the following steps:

[0033] (1) Pretreatment and pore division. Cut the graphite felt into small pieces with a side length of 2-3 cm. Use a tube furnace to heat at 200-240 °C for 1-2 h in a nitrogen atmosphere to remove impurities. Wash with anhydrous ethanol and deionized water 2-3 times. Mix 1 g of graphite felt with 100-200 mL of 0.5-1 mol / L sodium hydroxide solution and treat under magnetic stirring for 30-40 min. Use a tube furnace to heat at 760-780 °C for 2-3 h in a nitrogen atmosphere, and control the heating rate at 2-3 °C / min. After cooling to room temperature, mix 1 g of treated graphite felt with 100-200 mL of 1-2 mol / L sodium hydroxide solution and treat under magnetic stirring for 10-15 min. Use a tube furnace to heat at 760-780 °C for 2-3 h in a nitrogen atmosphere, and control the heating rate at 3-5 °C / min. After cooling to room temperature, the electrode was rinsed two to three times with 1 mol / L dilute hydrochloric acid and then with deionized water, then dried in a 60°C oven for 8 hours. Pore size distribution analysis revealed the formation of numerous small pores of two distinct ranges. Pores with diameters >1 μm serve as channels for the flow battery electrolyte, while pores with diameters between 5 and 100 nm provide numerous active sites for redox reactions. BET surface area analysis revealed that macropores with diameters >1 μm accounted for approximately 26.6% to 35.7%, while mesopores and macropores with diameters between 5 and 100 nm accounted for approximately 38.6% to 44.2%. Both pore sizes were uniformly distributed across the electrode surface.

[0034] (2) Loading neodymium oxide to improve electrochemical performance. Under magnetic stirring, 2.75-2.85 g of anhydrous neodymium nitrate, 1.26-1.34 g of anhydrous neodymium chloride and 0.28-0.36 g of polyamino acid were dissolved in a mixture of 50 mL of ethanol and isopropanol (the volume ratio of the two was 1-1.5:1). Then, 4.5-5.5 mL of ammonia water was added dropwise in a closed environment. According to the ratio of 1 g of the treated graphite felt obtained in step (1) and 15-25 mL of the above liquid, it was impregnated and dried in a nitrogen atmosphere after 1.5-2 h. Use a tube furnace to heat at 480-520 ° C for 2-3 h in a nitrogen atmosphere, and the heating rate was controlled at 3-5 ° C / min. After cooling to room temperature, it was washed 2-3 times with 1 mol / L dilute hydrochloric acid and deionized water respectively and placed in a 60 ° C oven to dry for 8 h. After calculation, the mass loading per unit area of ​​neodymium oxide is 0.17~0.19 mg / cm 2 After this treatment, the charge-discharge performance and energy efficiency are improved, with energy efficiency increasing by 5%, but the conductivity and stability are still insufficient.

[0035] (3) Load oxygen defect CoMnOx to further improve performance. Add 1.25~1.35 g potassium permanganate, 0.66~0.70 g manganese sulfate monohydrate, 0.57~0.61 g cobalt sulfate hexahydrate and 0.36~0.42 g sodium citrate to 35~45 mL deionized water and 5~15 mL anhydrous ethanol, and stir magnetically at 70~80°C for 30~40 minutes. Then add the mixed solution to the hydrothermal reactor and seal it, and keep it warm in an oven at 150~160°C for 8~10 hours. After natural cooling, the mixed slurry is evenly coated on the surface of the electrode sheet obtained in step (2), and the mass loading per unit area is 0.38~0.42 mg / cm 2 The samples were heated in a tube furnace at 390-430°C for 2.5-3 hours in a nitrogen atmosphere, with a heating rate of 2-3°C / min. After cooling to room temperature, the samples were rinsed two or three times with 1 mol / L dilute hydrochloric acid and then with deionized water, and then dried in a 60°C oven for 8 hours. This treatment further improved the charge-discharge performance and energy efficiency, as well as the conductivity and stability.

[0036] (4) Electrodeposit bismuth to enhance conductivity and stability. Under magnetic stirring, add 30-40 mL of 0.25-0.3 mol / L sodium carbonate, 30-40 mL of 0.28-0.32 mol / L potassium hydroxide, 0.23-0.29 g of 1-butyl-3-methylimidazole chloride, 1.8-2.2 g of bismuth oxide, and 3-5 mL of ethanolamine to the container and dilute to 1 L with deionized water. Use 3 mol / L potassium hydroxide solution to adjust the pH value to 13.6-14. Use this liquid as the electrolyte of the three-electrode system and place the electrode obtained in step (3) perpendicular to the flow direction of the electrolyte in the three-electrode system of the electrolytic cell. Use a pulse power supply to supply 2-3 A / dm 2 The pulse current density was cycled for several times and kept at 40-50℃, and the electrodeposition amount of bismuth was controlled at 0.26-0.30 mg / cm 2 After electrodeposition, the electrodes were rinsed several times with deionized water until the pH reached 7-8. The electrodes were then dried in a 60°C oven for 8 hours before testing. This treatment significantly improved the electrodes' electrochemical performance, conductivity, and stability.

[0037] Example 1

[0038] (1) Cut the graphite felt into small pieces with a side length of 2.5 cm. Use a tube furnace to heat at 220 °C for 1.5 h in a nitrogen atmosphere to remove impurities. Wash with anhydrous ethanol and deionized water three times. Mix 1 g of graphite felt with 150 mL of 0.75 mol / L sodium hydroxide solution and treat under magnetic stirring for 35 min. Use a tube furnace to heat at 770 °C for 2.5 h in a nitrogen atmosphere, and control the heating rate at 2.5 °C / min. After cooling to room temperature, mix 1 g of treated graphite felt with 150 mL of 1.5 mol / L sodium hydroxide solution and treat under magnetic stirring for 13 min. Use a tube furnace to heat at 770 °C for 2.5 h in a nitrogen atmosphere, and control the heating rate at 4 °C / min. After cooling to room temperature, wash with 1 mol / L dilute hydrochloric acid and deionized water three times respectively and place in a 60 °C oven to dry for 8 h. Pore size distribution test see Figure 1 Figure (a) shows the formation of a large number of small pores of two different sizes. Pores with a pore size >1 μm can serve as channels for the electrolyte in flow batteries, while pores with a pore size of 5-100 nm provide a large number of active sites for redox reactions.

[0039] (2) Under magnetic stirring, 2.80 g of anhydrous neodymium nitrate, 1.30 g of anhydrous neodymium chloride and 0.32 g of polyamino acid were dissolved in a mixture of 50 mL of ethanol and isopropanol (the volume ratio of the two was 1.25:1). Then, 5.0 mL of ammonia water was added dropwise in a closed environment. 1 g of the treated graphite felt obtained in step (1) was impregnated with 20 mL of the above liquid and dried in a nitrogen atmosphere after 2 h. A tube furnace was used to heat at 500 °C for 2.5 h in a nitrogen atmosphere, and the heating rate was controlled at 4 °C / min. After cooling to room temperature, it was washed three times with 1 mol / L dilute hydrochloric acid and deionized water respectively and placed in a 60 °C oven to dry for 8 h. After this treatment, the charge and discharge performance and energy efficiency were improved, and the energy efficiency could be increased by 5%, but the conductivity and stability were still insufficient.

[0040] (3) Add 1.30 g potassium permanganate, 0.68 g manganese sulfate monohydrate, 0.59 g cobalt sulfate hexahydrate, and 0.39 g sodium citrate to 40 mL deionized water and 10 mL anhydrous ethanol, and stir magnetically at 75°C for 35 minutes. Then, add the mixed solution to a hydrothermal reactor and seal it, and keep it in an oven at 155°C for 9 hours. After natural cooling, evenly apply the mixed slurry to the surface of the electrode sheet obtained in step (2), with a mass loading per unit area of ​​0.40 mg / cm 2The samples were heated at 410°C in a nitrogen atmosphere for 2.75 h in a tube furnace at a heating rate of 2.5°C / min. After cooling to room temperature, they were washed three times with 1 mol / L dilute hydrochloric acid and three times with deionized water, and then dried in a 60°C oven for 8 h. This treatment further enhanced the charge-discharge performance and energy efficiency, improved the conductivity and stability, and increased the number of stable cycles by nearly 350.

[0041] (4) Under magnetic stirring, add 35 mL of 0.28 mol / L sodium carbonate, 35 mL of 0.30 mol / L potassium hydroxide, 0.26 g of 1-butyl-3-methylimidazole chloride, 2.0 g of bismuth oxide, and 4 mL of ethanolamine to the container and dilute to 1 L with deionized water. Use 3 mol / L potassium hydroxide solution to adjust the pH value to 13.8. This liquid is used as the electrolyte of the three-electrode system and the electrode obtained in step (3) is placed perpendicular to the flow direction of the electrolyte in the electrolytic cell three-electrode system. A pulse power supply of 2.5 A / dm is used. 2 The pulse current density was cycled for several times and kept at 45 °C, and the electrodeposition amount of bismuth was controlled at 0.28 mg / cm 2 After electrodeposition, the electrodes were rinsed several times with deionized water until the pH reached 7.5. The electrodes were dried in a 60°C oven for 8 hours before testing. This treatment significantly improved the electrodes' electrochemical performance, conductivity, and stability, with energy efficiency increasing to 86.6% and the number of stable cycles significantly increasing to 1505.

[0042] Example 2

[0043] (1) Cut the graphite felt into small pieces with a side length of 2 cm. Use a tube furnace to heat at 240℃ for 1 h in a nitrogen atmosphere to remove impurities. Rinse with anhydrous ethanol and deionized water three times. Mix 1 g of graphite felt with 200 mL of 0.5 mol / L sodium hydroxide solution and treat under magnetic stirring for 40 min. Use a tube furnace to heat at 780℃ for 2 h in a nitrogen atmosphere, and the heating rate is controlled at 2℃ / min. After cooling to room temperature, mix 1 g of treated graphite felt with 200 mL of 1 mol / L sodium hydroxide solution and treat under magnetic stirring for 15 min. Use a tube furnace to heat at 780℃ for 2 h in a nitrogen atmosphere, and the heating rate is controlled at 3℃ / min. After cooling to room temperature, wash with 1 mol / L dilute hydrochloric acid and deionized water three times respectively and place in a 60℃ oven to dry for 8 h. The pore size distribution test shows that a large number of small pores of two different ranges are formed. Pores with a pore size >1 μm can serve as channels for the electrolyte in flow batteries, while pores with a pore size of 5-100 nm provide a large number of active sites for redox reactions.

[0044] (2) Under magnetic stirring, 2.75 g of anhydrous neodymium nitrate, 1.34 g of anhydrous neodymium chloride and 0.28 g of polyamino acid were dissolved in a mixture of 50 mL of ethanol and isopropanol (the volume ratio of the two was 1.5:1). Then, 5.5 mL of ammonia water was added dropwise in a closed environment. 1 g of the treated graphite felt obtained in step (1) was impregnated with 25 mL of the above liquid and dried in a nitrogen atmosphere after 2 h. A tube furnace was used to heat at 480 ° C for 3 h in a nitrogen atmosphere, and the heating rate was controlled at 5 ° C / min. After cooling to room temperature, it was washed twice with 1 mol / L dilute hydrochloric acid and deionized water respectively and placed in a 60 ° C oven to dry for 8 h. After this treatment, the charge and discharge performance and energy efficiency were improved, and the energy efficiency could be increased by 5%, but the conductivity and stability were still insufficient.

[0045] (3) Add 1.35 g potassium permanganate, 0.66 g manganese sulfate monohydrate, 0.61 g cobalt sulfate hexahydrate, and 0.36 g sodium citrate to 35 mL deionized water and 15 mL anhydrous ethanol, and stir magnetically at 80°C for 30 minutes. Then, add the mixed solution to a hydrothermal reactor and seal it, and keep it in an oven at 160°C for 8 hours. After natural cooling, evenly apply the mixed slurry to the surface of the electrode sheet obtained in step (2), with a mass loading per unit area of ​​0.42 mg / cm 2 The samples were heated at 390°C for 3 h in a nitrogen atmosphere using a tube furnace, with a heating rate of 3°C / min. After cooling to room temperature, they were washed three times with 1 mol / L dilute hydrochloric acid and three times with deionized water, and then dried in a 60°C oven for 8 h. This treatment further enhanced the charge-discharge performance and energy efficiency, improved the conductivity and stability, and increased the number of stable cycles by nearly 350.

[0046] (4) Under magnetic stirring, add 30 mL of 0.3 mol / L sodium carbonate, 30 mL of 0.32 mol / L potassium hydroxide, 0.23 g of 1-butyl-3-methylimidazole chloride, 2.2 g of bismuth oxide, and 5 mL of ethanolamine to the container and dilute to 1 L with deionized water. Use 3 mol / L potassium hydroxide solution to adjust the pH value to 14. This liquid is used as the electrolyte of the three-electrode system and the electrode obtained in step (3) is placed perpendicular to the flow direction of the electrolyte in the electrolytic cell three-electrode system. A pulse power supply of 2 A / dm is used. 2 The pulse current density was cycled for several times and kept at 50℃, and the electrodeposition amount of bismuth was controlled at 0.26 mg / cm 2 After electrodeposition, the electrodes were rinsed several times with deionized water until the pH reached 8. The electrodes were then dried in a 60°C oven for 8 hours before testing. This treatment significantly improved the electrochemical performance and stability of the electrodes, with energy efficiency increasing to 85.3% and the number of stable cycles increasing to 1441.

[0047] Example 3

[0048] (1) Cut the graphite felt into small pieces with a side length of 3 cm. Use a tube furnace to heat at 200 °C for 2 h in a nitrogen atmosphere to remove impurities. Rinse twice with anhydrous ethanol and deionized water. Mix 1 g of graphite felt with 100 mL of 1 mol / L sodium hydroxide solution and treat under magnetic stirring for 30 min. Use a tube furnace to heat at 760 °C for 3 h in a nitrogen atmosphere, and the heating rate is controlled at 3 °C / min. After cooling to room temperature, mix 1 g of treated graphite felt with 100 mL of 2 mol / L sodium hydroxide solution and treat under magnetic stirring for 10 min. Use a tube furnace to heat at 760 °C for 3 h in a nitrogen atmosphere, and the heating rate is controlled at 5 °C / min. After cooling to room temperature, wash twice with 1 mol / L dilute hydrochloric acid and deionized water respectively and place in a 60 °C oven to dry for 8 h. The pore size distribution test shows that a large number of small pores of two different ranges are formed. Pores with a pore size >1 μm can serve as channels for the electrolyte in flow batteries, while pores with a pore size of 5-100 nm provide a large number of active sites for redox reactions.

[0049] (2) Under magnetic stirring, 2.85 g of anhydrous neodymium nitrate, 1.26 g of anhydrous neodymium chloride and 0.36 g of polyamino acid were dissolved in a mixture of 50 mL of ethanol and isopropanol (the volume ratio of the two was 1:1). Then, 4.5 mL of ammonia water was added dropwise in a closed environment. 1 g of the treated graphite felt obtained in step (1) was impregnated with 15 mL of the above liquid and dried in a nitrogen atmosphere after 1.5 h. A tube furnace was used to heat at 520 ° C for 2 h in a nitrogen atmosphere, and the heating rate was controlled at 3 ° C / min. After cooling to room temperature, it was washed three times with 1 mol / L dilute hydrochloric acid and deionized water respectively and placed in a 60 ° C oven to dry for 8 h. After this treatment, the charge and discharge performance and energy efficiency were improved, and the energy efficiency could be increased by 5%, but the conductivity and stability were still insufficient.

[0050] (3) Add 1.25 g potassium permanganate, 0.70 g manganese sulfate monohydrate, 0.57 g cobalt sulfate hexahydrate, and 0.42 g sodium citrate to 45 mL deionized water and 5 mL anhydrous ethanol, and stir magnetically at 70°C for 40 minutes. Then, add the mixed solution to a hydrothermal reactor and seal it, and keep it in an oven at 150°C for 10 hours. After natural cooling, evenly apply the mixed slurry to the surface of the electrode sheet obtained in step (2), with a mass loading per unit area of ​​0.38 mg / cm 2The samples were heated at 430°C for 2.5 h in a nitrogen atmosphere using a tube furnace, with a heating rate of 2°C / min. After cooling to room temperature, they were washed twice with 1 mol / L dilute hydrochloric acid and then with deionized water, and dried in a 60°C oven for 8 h. This treatment further enhanced the charge-discharge performance and energy efficiency, improved the conductivity and stability, and increased the number of stable cycles by nearly 350.

[0051] (4) Under magnetic stirring, add 40 mL of 0.25 mol / L sodium carbonate, 40 mL of 0.28 mol / L potassium hydroxide, 0.29 g of 1-butyl-3-methylimidazole chloride, 1.8 g of bismuth oxide, and 3 mL of ethanolamine to the container and dilute to 1 L with deionized water. Use 3 mol / L potassium hydroxide solution to adjust the pH value to 13.6. This liquid is used as the electrolyte of the three-electrode system and the electrode obtained in step (3) is placed perpendicular to the flow direction of the electrolyte in the electrolytic cell three-electrode system. A pulse power supply of 3A / dm is used. 2 The pulse current density was cycled for several times and kept at 40℃, and the electrodeposition amount of bismuth was controlled at 0.30 mg / cm 2 After electrodeposition, the electrodes were rinsed several times with deionized water until the pH reached 7. The electrodes were then dried in a 60°C oven for 8 hours before testing. After this treatment, the electrode's energy efficiency increased to 85.6%, and the number of stable cycles increased to 1452.

[0052] Comparative Example 1: No holes

[0053] (1) Cut the graphite felt into small pieces with a side length of 2.5 cm. Heat them in a tube furnace at 220°C for 1.5 h in a nitrogen atmosphere to remove impurities. Rinse them three times with anhydrous ethanol and deionized water.

[0054] (2) Dissolve 2.80 g of anhydrous neodymium nitrate, 1.30 g of anhydrous neodymium chloride, and 0.32 g of polyamino acid in a mixture of 50 mL of ethanol and isopropanol (volume ratio of the two is 1.25:1) under magnetic stirring. Then, add 5.0 mL of ammonia water dropwise in a sealed environment. Impregnate 1 g of the treated graphite felt obtained in step (1) with 20 mL of the above liquid, and dry it in a nitrogen atmosphere after 2 h. Heat it at 500 °C in a nitrogen atmosphere in a tube furnace for 2.5 h, with a heating rate of 4 °C / min. After cooling to room temperature, wash it three times with 1 mol / L dilute hydrochloric acid and deionized water, respectively, and dry it in a 60 °C oven for 8 h.

[0055] (3) Add 1.30 g potassium permanganate, 0.68 g manganese sulfate monohydrate, 0.59 g cobalt sulfate hexahydrate, and 0.39 g sodium citrate to 40 mL deionized water and 10 mL anhydrous ethanol, and stir magnetically at 75°C for 35 minutes. Then, add the mixed solution to a hydrothermal reactor and seal it, and keep it in an oven at 155°C for 9 hours. After natural cooling, evenly apply the mixed slurry to the surface of the electrode sheet obtained in step (2), with a mass loading per unit area of ​​0.40 mg / cm 2 The sample was heated in a tube furnace at 410°C for 2.75 h in a nitrogen atmosphere at a heating rate of 2.5°C / min. After cooling to room temperature, it was rinsed three times with 1 mol / L dilute hydrochloric acid and three times with deionized water, and then dried in a 60°C oven for 8 h.

[0056] (4) Under magnetic stirring, add 35 mL of 0.28 mol / L sodium carbonate, 35 mL of 0.30 mol / L potassium hydroxide, 0.26 g of 1-butyl-3-methylimidazole chloride, 2.0 g of bismuth oxide, and 4 mL of ethanolamine to the container and dilute to 1 L with deionized water. Use 3 mol / L potassium hydroxide solution to adjust the pH value to 13.8. This liquid is used as the electrolyte of the three-electrode system and the electrode obtained in step (3) is placed perpendicular to the flow direction of the electrolyte in the electrolytic cell three-electrode system. A pulse power supply of 2.5 A / dm is used. 2 The pulse current density was cycled for several times and kept at 45 °C, and the electrodeposition amount of bismuth was controlled at 0.28 mg / cm 2 After electrodeposition, the electrodes were rinsed several times with deionized water until the pH reached 7.5. The electrodes were dried in a 60°C oven for 8 hours before testing. After this treatment, the electrodes achieved an energy efficiency of 83.8% and a stable cycle life of 1264 cycles.

[0057] Comparative Example 2: Only split the holes and reduce the sodium hydroxide concentration

[0058] Graphite felt was cut into small pieces with a side length of 2.5 cm. Impurities were removed by heating at 220°C in a tube furnace for 1.5 h. The pieces were then washed three times with anhydrous ethanol and deionized water. Each gram of graphite felt was mixed with 150 mL of 0.25 mol / L sodium hydroxide solution and treated with magnetic stirring for 35 min. The pieces were then heated at 770°C in a tube furnace for 2.5 h at a heating rate of 2.5°C / min. After cooling to room temperature, each gram of the treated graphite felt was mixed with 150 mL of 0.5 mol / L sodium hydroxide solution and treated with magnetic stirring for 13 min. The pieces were then heated at 770°C in a tube furnace for 2.5 h at a heating rate of 4°C / min. After cooling to room temperature, the pieces were washed three times with 1 mol / L dilute hydrochloric acid and three times with deionized water, and dried in a 60°C oven for 8 h. After this treatment, the energy efficiency of the electrode is low, about 74.0%; the number of stable cycles is also low, about 779 times.

[0059] Comparative Example 3: Only dividing the holes and increasing the sodium hydroxide concentration

[0060] Graphite felt was cut into 2.5 cm squares. Impurities were removed by heating at 220°C in a tube furnace for 1.5 h. The sample was then washed three times with anhydrous ethanol and deionized water. One gram of graphite felt was mixed with 150 mL of 2 mol / L sodium hydroxide solution and treated with magnetic stirring for 35 min. The sample was then heated at 770°C in a tube furnace for 2.5 h at a heating rate of 2.5°C / min. After cooling to room temperature, one gram of the treated graphite felt was mixed with 150 mL of 4 mol / L sodium hydroxide solution and treated with magnetic stirring for 13 min. The sample was then heated at 770°C in a tube furnace for 2.5 h at a heating rate of 4°C / min. After cooling to room temperature, the sample was washed three times with 1 mol / L dilute hydrochloric acid and three times with deionized water, and then dried in a 60°C oven for 8 h. The electrode exhibited a low energy efficiency of approximately 74.9% after this treatment, and the number of stable cycles was only 532.

[0061] Comparative Example 4: Only hole division

[0062] Graphite felt was cut into 2.5 cm squares. Impurities were removed by heating at 220°C in a tube furnace for 1.5 h. The sample was then washed three times with anhydrous ethanol and deionized water. Each gram of graphite felt was mixed with 150 mL of 0.75 mol / L sodium hydroxide solution and treated with magnetic stirring for 35 min. The sample was then heated at 770°C in a tube furnace for 2.5 h at a heating rate of 2.5°C / min. After cooling to room temperature, each gram of the treated graphite felt was mixed with 150 mL of 1.5 mol / L sodium hydroxide solution and treated with magnetic stirring for 13 min. The sample was then heated at 770°C in a tube furnace for 2.5 h at a heating rate of 4°C / min. After cooling to room temperature, the sample was washed three times with 1 mol / L dilute hydrochloric acid and three times with deionized water, and then dried in a 60°C oven for 8 h. After this treatment, the energy efficiency of the electrode is low, about 74.6%; the number of stable cycles is also low, about 772 times.

[0063] Comparative Example 5: No Bismuth Deposition

[0064] (1) Cut the graphite felt into small pieces with a side length of 2.5 cm. Use a tube furnace to heat at 220℃ for 1.5 hours in a nitrogen atmosphere to remove impurities. Rinse with anhydrous ethanol and deionized water three times. Mix 1 g of graphite felt with 150 mL of 0.75 mol / L sodium hydroxide solution and treat under magnetic stirring for 35 minutes. Use a tube furnace to heat at 770℃ for 2.5 hours in a nitrogen atmosphere, and the heating rate is controlled at 2.5℃ / min. After cooling to room temperature, mix 1 g of the treated graphite felt with 150 mL of 1.5 mol / L sodium hydroxide solution and treat under magnetic stirring for 13 minutes. Use a tube furnace to heat at 770℃ for 2.5 hours in a nitrogen atmosphere, and the heating rate is controlled at 4℃ / min. After cooling to room temperature, wash with 1 mol / L dilute hydrochloric acid and deionized water three times respectively and place in a 60℃ oven to dry for 8 hours. The pore size distribution test shows that a large number of small pores of two different ranges are formed. Pores with a pore size >1 μm can serve as channels for the electrolyte in flow batteries, while pores with a pore size of 5-100 nm provide a large number of active sites for redox reactions.

[0065] (2) Dissolve 2.80 g of anhydrous neodymium nitrate, 1.30 g of anhydrous neodymium chloride, and 0.32 g of polyamino acid in a mixture of 50 mL of ethanol and isopropanol (volume ratio of the two is 1.25:1) under magnetic stirring. Then, add 5.0 mL of ammonia water dropwise in a sealed environment. Impregnate 1 g of the treated graphite felt obtained in step (1) with 20 mL of the above liquid, and dry it in a nitrogen atmosphere after 2 h. Heat it at 500 °C in a nitrogen atmosphere in a tube furnace for 2.5 h, with a heating rate of 4 °C / min. After cooling to room temperature, wash it three times with 1 mol / L dilute hydrochloric acid and deionized water, respectively, and dry it in a 60 °C oven for 8 h.

[0066] (3) Add 1.30 g potassium permanganate, 0.68 g manganese sulfate monohydrate, 0.59 g cobalt sulfate hexahydrate, and 0.39 g sodium citrate to 40 mL deionized water and 10 mL anhydrous ethanol, and stir magnetically at 75°C for 35 minutes. Then, add the mixed solution to a hydrothermal reactor and seal it, and keep it in an oven at 155°C for 9 hours. After natural cooling, evenly apply the mixed slurry to the surface of the electrode sheet obtained in step (2), with a mass loading per unit area of ​​0.40 mg / cm 2 The electrode was heated at 410°C in a nitrogen atmosphere for 2.75 hours in a tube furnace at a heating rate of 2.5°C / min. After cooling to room temperature, it was rinsed three times with 1 mol / L dilute hydrochloric acid and three times with deionized water, and then dried in a 60°C oven for 8 hours. The electrode was then tested. After this treatment, the electrode achieved an energy efficiency of 82.2% and a stable cycle life of 1385 cycles.

[0067] Comparative Example 6: Oxygen-Defect-Free CoMnOx Loading and Electrodeposition of Bismuth

[0068] (1) Cut the graphite felt into small pieces with a side length of 2.5 cm. Use a tube furnace to heat at 220℃ for 1.5 hours in a nitrogen atmosphere to remove impurities. Rinse with anhydrous ethanol and deionized water three times. Mix 1 g of graphite felt with 150 mL of 0.75 mol / L sodium hydroxide solution and treat under magnetic stirring for 35 minutes. Use a tube furnace to heat at 770℃ for 2.5 hours in a nitrogen atmosphere, and the heating rate is controlled at 2.5℃ / min. After cooling to room temperature, mix 1 g of the treated graphite felt with 150 mL of 1.5 mol / L sodium hydroxide solution and treat under magnetic stirring for 13 minutes. Use a tube furnace to heat at 770℃ for 2.5 hours in a nitrogen atmosphere, and the heating rate is controlled at 4℃ / min. After cooling to room temperature, wash with 1 mol / L dilute hydrochloric acid and deionized water three times respectively and place in a 60℃ oven to dry for 8 hours. The pore size distribution test shows that a large number of small pores of two different ranges are formed. Pores with a pore size >1 μm can serve as channels for the electrolyte in flow batteries, while pores with a pore size of 5-100 nm provide a large number of active sites for redox reactions.

[0069] (2) Under magnetic stirring, 2.80 g of anhydrous neodymium nitrate, 1.30 g of anhydrous neodymium chloride and 0.32 g of polyamino acid were dissolved in a mixture of 50 mL of ethanol and isopropanol (the volume ratio of the two was 1.25:1). Then, 5.0 mL of ammonia water was added dropwise in a closed environment. 1 g of the treated graphite felt obtained in step (1) was impregnated with 20 mL of the above liquid and dried in a nitrogen atmosphere after 2 h. A tube furnace was used to heat at 500 °C for 2.5 h in a nitrogen atmosphere, with a heating rate of 4 °C / min. After cooling to room temperature, the electrode was washed three times with 1 mol / L dilute hydrochloric acid and deionized water respectively and dried in a 60 °C oven for 8 h. After this treatment, the energy efficiency of the electrode reached 79.5%, and the number of stable cycles could reach 1128 times.

[0070] Comparative Example 7: Oxygen-Deficient CoMnOx Loading and Electrodeposition of Bismuth with Reduced Neodymium Loading

[0071] (1) Cut the graphite felt into small pieces with a side length of 2.5 cm. Use a tube furnace to heat at 220 °C for 1.5 h in a nitrogen atmosphere to remove impurities. Rinse with anhydrous ethanol and deionized water three times. Mix 1 g of graphite felt with 150 mL of 0.75 mol / L sodium hydroxide solution and treat under magnetic stirring for 35 min. Use a tube furnace to heat at 770 °C for 2.5 h in a nitrogen atmosphere, with a heating rate of 2.5 °C / min. After cooling to room temperature, mix 1 g of treated graphite felt with 150 mL of 1.5 mol / L sodium hydroxide solution and treat under magnetic stirring for 13 min. Use a tube furnace to heat at 770 °C for 2.5 h in a nitrogen atmosphere, with a heating rate of 4 °C / min. After cooling to room temperature, wash with 1 mol / L dilute hydrochloric acid and deionized water three times and place in a 60 °C oven to dry for 8 h.

[0072] (2) Under magnetic stirring, 1.40 g of anhydrous neodymium nitrate, 0.65 g of anhydrous neodymium chloride, and 0.32 g of polyamino acid were dissolved in a mixture of 50 mL of ethanol and isopropanol (the volume ratio of the two was 1.25:1). Then, 5.0 mL of ammonia water was added dropwise in a closed environment. 1 g of the treated graphite felt obtained in step (1) was impregnated with 20 mL of the above liquid and dried in a nitrogen atmosphere after 2 h. A tube furnace was used to heat at 500 °C for 2.5 h in a nitrogen atmosphere, with a heating rate of 4 °C / min. After cooling to room temperature, the electrode was washed three times with 1 mol / L dilute hydrochloric acid and deionized water, respectively, and dried in a 60 °C oven for 8 h. After this treatment, the energy efficiency of the electrode reached 77.6%, and the number of stable cycles could reach 1092 times.

[0073] Comparative Example 8: Oxygen-Deficient CoMnOx Loading and Electrodeposition of Bismuth and Increasing Neodymium Loading

[0074] (1) Cut the graphite felt into small pieces with a side length of 2.5 cm. Use a tube furnace to heat at 220 °C for 1.5 h in a nitrogen atmosphere to remove impurities. Rinse with anhydrous ethanol and deionized water three times. Mix 1 g of graphite felt with 150 mL of 0.75 mol / L sodium hydroxide solution and treat under magnetic stirring for 35 min. Use a tube furnace to heat at 770 °C for 2.5 h in a nitrogen atmosphere, with a heating rate of 2.5 °C / min. After cooling to room temperature, mix 1 g of treated graphite felt with 150 mL of 1.5 mol / L sodium hydroxide solution and treat under magnetic stirring for 13 min. Use a tube furnace to heat at 770 °C for 2.5 h in a nitrogen atmosphere, with a heating rate of 4 °C / min. After cooling to room temperature, wash with 1 mol / L dilute hydrochloric acid and deionized water three times and place in a 60 °C oven to dry for 8 h.

[0075] (2) Under magnetic stirring, 5.60 g of anhydrous neodymium nitrate, 2.60 g of anhydrous neodymium chloride and 0.32 g of polyamino acid were dissolved in a mixture of 50 mL of ethanol and isopropanol (the volume ratio of the two was 1.25:1). Then, 5.0 mL of ammonia water was added dropwise in a closed environment. 1 g of the treated graphite felt obtained in step (1) was impregnated with 20 mL of the above liquid and dried in a nitrogen atmosphere after 2 h. A tube furnace was used to heat at 500 °C for 2.5 h in a nitrogen atmosphere, with a heating rate of 4 °C / min. After cooling to room temperature, the electrode was washed three times with 1 mol / L dilute hydrochloric acid and deionized water respectively and dried in a 60 °C oven for 8 h. After this treatment, the energy efficiency of the electrode reached 78.1%, and the number of stable cycles could reach 1087 times.

[0076] Comparative Example 9: Original Electrode

[0077] The graphite felt was cut into small pieces with a side length of 2.5 cm. Impurities were removed by heating at 220°C in a nitrogen atmosphere for 1.5 h in a tube furnace. The electrode was then rinsed three times with anhydrous ethanol and deionized water. After this treatment, the electrode had the lowest energy efficiency, approximately 72.3%, and the lowest number of stable cycles, approximately 345.

[0078] Table 1. Performance comparison of various examples and comparative examples

[0079] .

[0080] The voltage efficiency, energy efficiency, specific surface area, and cycle stability times of Examples 1-3 showed no significant differences, and all values ​​were higher than those of Comparative Examples 1-5. This indicates that the electrochemical performance and stability of the electrodes were significantly improved after pretreatment and pore separation, loading with neodymium oxide to enhance electrochemical performance, loading with oxygen-deficient CoMnOx to further enhance performance, and electrodeposition of bismuth to enhance conductivity and stability.

[0081] The difference between Comparative Example 1 and Example 1 is that the former does not implement the pore adjustment of step (1), and the subsequent metal loading steps are the same. Compared with Example 1, the voltage efficiency and energy efficiency of Comparative Example 1 decreased slightly, decreasing by 1.7% and 2.8% respectively, indicating that the subsequent metal loading is a key factor in promoting the improvement of electrochemical performance. The decrease may be related to the specific surface area. The specific surface area of ​​Comparative Example 1 is about 44% lower than that of Example 1, which has an adverse effect on the uniformity of subsequent metal loading and the full exposure of active sites, thereby causing a decrease in the uniformity and stability of the loaded metal, and thus also causing a decrease in cycle stability (19%), indicating that the pore adjustment in step (1) is necessary.

[0082] Compared with Comparative Example 6, Comparative Example 4 does not implement step (1), that is, there is no loading of neodymium oxide. Compared with Example 1, only the pore adjustment of step (1) remains. Neodymium oxide, as a new type of catalytic metal oxide, can form Lewis acids with acid ions, combine and separate with the diffuse redox couple participating in the reaction, and adjust the reaction potential. It also acts as an oxygen binder to improve electrochemical performance by participating in the catalytic reaction. Comparative Example 4 does not have any catalytic metal loading and only involves physical adjustment of the pores. Therefore, various performances are lower than those of Comparative Example 6, such as a 4.9% decrease in energy efficiency, a 1.2% decrease in voltage efficiency, and a 356-fold decrease in cycle stability, while the specific surface area does not differ much.

[0083] Compared with Comparative Example 2 and Comparative Example 4, the concentrations of sodium hydroxide in the two treatments were reduced to half of the lower limit of the optimal treatment concentration range. The test results showed that compared with Comparative Example 2 and Comparative Example 4, the voltage efficiency and energy efficiency were slightly reduced, and the specific surface area was increased from 68.6 m 2 / g decreased to 49.2 m 2 / g, the difference in cycle stability is not large. This shows that when the concentration of sodium hydroxide treatment is insufficient, the number of pores will not meet the requirements, so the electrochemical performance is reduced. Compared with Comparative Example 3 and Comparative Example 4, the sodium hydroxide concentrations are increased to twice the upper limit of the optimal treatment concentration range, and the test results show that compared with Comparative Example 3 and Comparative Example 4, the voltage efficiency, energy efficiency and specific surface area are improved less, and the cycle stability is reduced from 772 times to 532 times. When the sodium hydroxide concentration is too high, the treatment of the electrode is more thorough. Although the electrochemical performance is slightly improved, the corrosion of the electrode is more serious and the cycle stability is significantly reduced, which is obviously unacceptable.

[0084] Compared with Example 1, in Comparative Example 5, step (4), i.e., the electrodeposition of bismuth, was not implemented. The voltage efficiency decreased by 2.1%, the energy efficiency decreased by 4.4%, the specific surface area decreased slightly, and the cycle stability decreased by 120 times. The reason is that the electrodeposition of bismuth can further improve the conductivity and stability of the electrode. Bismuth has the advantages of low toxicity, low cost, high conductivity, and high acid resistance. The bismuth-based material deposited by electrodeposition has good catalytic performance for the redox reaction of the electrode and provides a larger active area. The coupling of cobalt and manganese metal improves the catalytic activity, reduces the reaction overpotential, and inhibits the hydrogen evolution reaction in the electrochemical process.

[0085] Compared with Comparative Example 5, Comparative Example 6 did not implement step (3), that is, after loading neodymium oxide, oxygen-deficient CoMnOx was not loaded. Cobalt and manganese, as catalytic metals, can participate in the redox reaction. More importantly, the combination of oxygen defects and neodymium oxide in step (2) can form a relatively stable chemical bond, thereby maximizing the electrochemical performance and stability. By loading cobalt manganese oxide with oxygen defects, the bonding between neodymium and the electrode can be improved and the active sites can be optimized. Therefore, compared with Comparative Example 5, the voltage efficiency and energy efficiency of Comparative Example 6 decreased slightly, and the cycle stability decreased by 257 times.

[0086] Comparative Example 7, compared to Comparative Example 6, reduces the amount of both neodymium-containing substrates to half of their optimal usage. Test results show that compared to Comparative Example 6, the voltage efficiency, energy efficiency, specific surface area, and cycling stability are slightly reduced in Comparative Example 7. This indicates that insufficient neodymium oxide loading will not effectively improve charge-discharge performance and energy efficiency. Comparative Example 8, compared to Comparative Example 6, increases the amount of both neodymium-containing substrates to twice their optimal usage. Test results show that compared to Comparative Example 6, the voltage efficiency, energy efficiency, specific surface area, and cycling stability are slightly reduced in Comparative Example 8. This is because excessive neodymium oxide loading occupies too many active sites and strongly binds to oxygen, which in turn reduces conductivity and electrochemical performance.

[0087] Compared with Comparative Example 4, Comparative Example 9 did not control the pores, but only pretreated the original graphite felt electrode by cleaning. Therefore, the specific surface area was only 39% of that of Comparative Example 4, and it lacked sufficient reaction specific surface area, catalytically active substances, and active sites. Therefore, the electrochemical performance and cycle stability were both the lowest. The energy efficiency was approximately 14.3% lower than that of Example 1, and the cycle stability was only 22.9% of that of Example 1. This shows that Example 1 significantly improved the electrochemical performance and stability of the original electrode. Example 1 is a feasible and promising electrode treatment method for flow battery electrodes.

[0088] The present invention provides a pore-size-adjusted and metal-loaded graphite felt flow battery electrode, which comprises the following steps:

[0089] (1) After the graphite felt is cut and impurities are removed, it is treated with sodium hydroxide and then treated at high temperature. The above treatment method is repeated twice, and then cooled and dried to obtain an aperture adjustment electrode;

[0090] (2) Adding anhydrous neodymium nitrate, anhydrous neodymium chloride, and polyamino acid dissolved in ethanol to the above electrode and dripping ammonia water, soaking and drying, then high-temperature treatment and cooling and drying to obtain a neodymium oxide-modified electrode material;

[0091] (3) coating the above electrode with a mixture of potassium permanganate, manganese sulfate monohydrate, cobalt sulfate hexahydrate, sodium citrate and ethanol, treating the mixture at high temperature and cooling and drying the mixture to obtain an oxygen-deficient CoMnOx loaded electrode;

[0092] (4) The above electrode was immersed in a mixture of sodium carbonate, potassium hydroxide, 1-butyl-3-methylimidazole chloride, bismuth oxide and ethanolamine, the pH was adjusted and pulse current deposition was performed, and after cleaning and drying, a new graphite felt electrode with bismuth deposition was obtained.

[0093] By optimizing the chemical reagent dosage and processing parameters in the examples, minor improvements in voltage efficiency, energy efficiency, specific surface area, and cycle stability were achieved. Key factors influencing the performance of the examples include the pre-treatment pore separation parameters, the amount of neodymium oxide loaded, the amount of oxygen-deficient CoMnOx loaded and the ratio of cobalt to manganese, and the amount of electrodeposited bismuth. 1) The sodium hydroxide content and treatment temperature in the pre-treatment pore separation were optimized. Too low a sodium hydroxide content will not produce the desired pore size and diameter, while too high a content will cause excessive corrosion of the electrode material. Similarly, the temperature selection also balances pore size and material quality. 2) The amount of neodymium oxide loaded was also optimized. Insufficient neodymium oxide loading in the formulation will not effectively improve charge-discharge performance and energy efficiency. Excessive loading will occupy too many active sites and strongly bind to oxygen, thereby reducing conductivity and electrochemical performance. 3) The amount of oxygen-deficient CoMnOx loaded and the ratio of cobalt to manganese were also optimized. Cobalt and manganese are two active sites for redox reactions, and their ratio directly affects the reaction activity and kinetics. When the content of one of the metals is too high, the movement of the reaction center to the active site is inhibited, and thus the reaction performance is not improved. In addition, the appropriate number of oxygen defects is also important. Oxygen defects that are more consistent with the amount of neodymium oxide can form more stable chemical bonds, thereby maximizing the electrochemical performance and stability. 4) The amount of electrodeposited bismuth is also an important factor affecting the performance of the electrode, so it is optimized. When its amount is insufficient, the electrochemical performance and stability cannot be effectively improved. When its amount is too high, it will hinder the performance of neodymium oxide and oxygen defect sites, and may even cause performance degradation. The above parameters have been optimized to maximize the electrochemical performance and stability. The voltage efficiency of several embodiments is 87.8~88.7%, the energy efficiency is 85.3~86.6%, and the specific surface area is 72.8~75.6 m 2 / g, and the cycle stability is 1441~1505 times, and Example 1 is the highest performance group.

[0094] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A method for preparing a pore-size-adjusted and metal-loaded graphite felt flow battery electrode, characterized in that: The following steps are included: Step (1), pretreatment and pore separation: mixing the graphite felt with alkali solution, magnetically stirring and then heating, cooling to room temperature and then mixing with alkali solution again, magnetically stirring and heating again to obtain a pore separation material; Step (2), loading neodymium oxide: dissolving neodymium salt and polyamino acid in an alcohol solution, adding ammonia water dropwise and immersing the porous material therein, heating, washing and drying to obtain a neodymium oxide-modified electrode material; Step (3), loading oxygen-deficient CoMnOx: applying a mixed slurry containing manganese and cobalt on an electrode sheet, heating, washing, and drying to obtain an oxygen-deficient CoMnOx loaded electrode; Step (4), bismuth deposition: 1-butyl-3-methylimidazole chloride and bismuth oxide are dissolved in alkaline solution to form a three-electrode system electrolyte, the electrode loaded with oxygen defect CoMnOx is electroplated, and the bismuth-deposited graphite felt electrode is obtained by washing and drying.

2. The method for preparing a pore-size-adjusted and metal-loaded graphite felt flow battery electrode according to claim 1, characterized in that: In step (1), the alkali solution includes sodium hydroxide, and the sodium hydroxide treatment is first performed by mixing 1 g of graphite felt with 100-200 mL of 0.5-1 mol / L sodium hydroxide solution and treating under magnetic stirring for 30-40 min; the second treatment method is the same, only the concentration of the sodium hydroxide solution is adjusted to 1-2 mol / L.

3. The method for preparing a pore-size-adjusted and metal-loaded graphite felt flow battery electrode according to claim 1, characterized in that: In step (1), the heating is performed for the first time at 760-780°C in a nitrogen atmosphere for 2-3 h, with the heating rate controlled at 2-3°C / min. The second treatment temperature remains unchanged, with the heating rate controlled at 3-5°C / min.

4. The method for preparing a pore-size-adjusted and metal-loaded graphite felt flow battery electrode according to claim 1, characterized in that: In step (2), the neodymium salt includes one or more of neodymium nitrate and neodymium chloride, the alcohol solution includes one or more of ethanol and isopropanol, and the heating is carried out in a nitrogen atmosphere at 480-520°C for 2-3 h, with the heating rate controlled at 3-5°C / min.

5. The method for preparing a pore-size-adjusted and metal-loaded graphite felt flow battery electrode according to claim 4, characterized in that: In step (2), the mass loading per unit area of ​​neodymium oxide is 0.17~0.19 mg / cm 2 .

6. The method for preparing a pore-size-adjusted and metal-loaded graphite felt flow battery electrode according to claim 1, characterized in that: In step (3), the mixed slurry containing manganese and cobalt is obtained by adding potassium permanganate, manganese sulfate, cobalt sulfate and sodium citrate to water and ethanol, and performing a hydrothermal reaction in an oven at 150-160° C. for 8-10 h.

7. The method for preparing a pore-size-adjusted and metal-loaded graphite felt flow battery electrode according to claim 6, characterized in that: The coating mass loading per unit area of ​​the mixed slurry is 0.38-0.42 mg / cm 2 The heating is performed at 390-430° C. for 2.5-3 h, with a heating rate of 2-3° C. / min.

8. The method for preparing a pore-size-adjusted and metal-loaded graphite felt flow battery electrode according to claim 1, characterized in that: In step (4), the three-electrode system electrolyte is an aqueous solution of sodium carbonate, potassium hydroxide, 1-butyl-3-methylimidazole chloride, bismuth oxide and ethanolamine, with a pH of 13.6-14.

9. The method for preparing a pore-size-adjusted and metal-loaded graphite felt flow battery electrode according to claim 1, characterized in that: In step (4), the electrodeposition is carried out at 2~3 A / dm 2 The pulse current density was repeated for several cycles, and the temperature was kept at 40-50°C to control the electrodeposition amount of bismuth to 0.26-0.30 mg / cm 2 .

Citation Information

Patent Citations

  • Water-based zinc-manganese single flow battery

    CN105336971A

  • NiCo2O4 / carbon nanotube composite electrode material and preparation method thereof

    CN108376614A

Cited By

  • Electrode suitable for organic flow battery and preparation method thereof

    CN121641999A